STUDENT TEAMS-ACHIEVEMENT DIVISION TO IMPROVE STUDENTS’ WRITING SKILL - Sri Wahyuni (State Institute of Islamic Studies (IAIN) Salatiga, 2014)
Acquiring writing skill needs a lot of practices, and to produce a piece of writing needs a long process; hence, the appropriate method of the teaching and learning is very important to help students master writing skill. This article aims at reporting a research on the implementation of Student Teams-Achievement Division (STAD) as an alternative teaching method to improve students’ writing skill. Through Classroom Action Research design, the researcher did the research at fourth semester students of English Education study program of STAIN Kediri in academic year 2012-1013. The research procedures are planning, implementing, observing, and reflecting. The findings show that the implementation of STAD can improve the students’ writing skill which were indicated by the high percentage of the students’ active involvement and positive response on the implementation, and the students’ product of writing in which all of writing components can achieve good level in marking scheme as the minimum level.